Pediatric palliative care in cancer patients (Research, Society and Development, 2022)
Pediatric cancer has become one of the most relevant diseases of modernity, affecting millions of people and providing limitations. In this scenario, palliative care (PC) plays an important role, by reducing pain and increasing dignity from a multidisciplinary team, social and family support. But unlike adult cancer patients who have a collection of medical literature, pediatric patients are not approached with the same emphasis. Thus, the aim of the present study was to analyze the relevance of the work of a specialized team and the use of therapies related to pediatric palliative care (PPC) in cancer patients. This is an integrative review using articles searched in PubMed and Virtual Health Library databases. The descriptors used in the searches were: “palliative care”, “neoplasms”, “children” and “pain”. A total of 133 references were obtained that addressed the proposed theme, from which 16 studies were analyzed and selected that addressed the theme specifically addressed. Thus, studies related to the implementation of complementary therapies in PHC indicate that their early integration promotes better symptom control and lower incidence of depression, due to the psychosocial, physical, and emotional care offered to patients. There is a lack of studies on the subject and adequate training of multidisciplinary teams that affect the advancement of palliative care. Thus, new research must be developed to support treatment aimed at children and support the preparation of professionals, to suppress the mistaken understanding that this treatment is only useful at the end of life and generate greater adherence of families to improve the quality of life. patients' quality of life.